Innovative surface engineering technique for surface modification of Mg alloy for orthopedic application - Razak, M.A.A. (Springer International Publishing, 2019)
Biodegradable materials are required for the development of bone fixation accessories. Mg was recently identified to be biodegradable material and a better alternative for temporary implants application. However, the Mg alloy corrosion rate must be suitable for the application as biodegradable orthopedic implants. Controlling the Mg alloy corrosion rate is not easy. It is hypothesized that the Mg alloy-machined surface corrosion rate is possible to be controlled by manipulating the powder mixed electro-discharge machining (PMEDM) setting parameters. Therefore, this chapter aims at generating a method on how to determine the correct combination of PMEDM setting parameters to obtain a specific corrosion rate of Mg alloy. An opened-loop PMEDM dielectric circulation system is employed in the experiments. The setting parameters involved in the experiments include Zn particles concentration (Pcon), peak current (Pc), pulse-on time (Ton) and pulse-off time (Toff). The experiment results reveal that the Zn particles suspended in the dielectric fluid providing a bridge for uniform discharge energy on the Mg alloy. It results in a lower surface roughness which then leads to a lower corrosion rate due to smaller exposed surface area to the solution. Since the response output is influenced by the interaction among the setting parameters, an equation to determine the corrosion rate of Mg alloy-machined surface is generated by manipulating the value combination of those four setting parameters. With all the evidence presented in this chapter, it is proven that the Mg alloy-machined surface corrosion rate can be controlled by manipulating the PMEDM setting parameters. Â© Springer Nature Switzerland AG 2019.